Development of a HOTS-Leveled Two-Tier Multiple Choice (TTMC) Test to Measure Student Misconceptions in Islamic Studies - Humaidi, M. Nurul; Triansyah, Fadli Agus; Sugianto, Rahmad; Laila, Alfi Rachma Nisfi (CV. BImbingan Belajar Assyfa, 2023)
This study aims to develop a Two-Tier Multiple Choice (TTMC) HOTS-level test to measure student misconceptions in Islamic learning. The research method used is the 4-D method by Thiagarajan with descriptive data analysis. The results of the misconception test using TTMC showed variations in students' answers between those who understood the concept, had a pure misconception, guessed the misconception, and did not understand the concept. The feasibility of the evaluation tool is met, and the identification of misconceptions is divided into four categories. The percentage of students who understand the concept is 49%, pure misconception is 11%, guesses the misconception is 17%, and does not understand the concept is 23%. This study contributes to measuring students' misconceptions in Islamic learning and can be used to improve teaching effectiveness and students' understanding of concepts